The differential gut microbiota and their MetaCyc pathways in IBRV infected Angus calves - Yi, Pengfei; Li, Tianqing; Xu, Lianping; Li, Xin; Wang, Haiyan; Ma, Yingcai; Ma, Yunxiao; Sun, Yawei; Li, Na; Zhong, Qi; Ma, Xuelian; Yao, Gang (Frontiers in Microbiology, 2025)
Infectious bovine rhinotracheitis virus (IBRV) is a globally prevalent pathogen that causes respiratory disease in cattle. Emerging evidence suggests that specific bacterial taxa and gut microbial community compositions are strongly associated with viral pathogenesis, by either enhancing or mitigating disease outcomes. This not only impacts the host’s gastrointestinal physiology but also affects distant organs, including the lungs, liver, and brain. However, the impact of IBRV infection on changes in gut microbiota composition and its association with MetaCyc metabolic pathways remains poorly understood. In this study, based on an epidemiological survey of one-month-old Angus calves in a large-scale Angus beef cattle breeding farm consists of four breeding areas located in Maigaiti County of Kashi Prefecture, China. Alterations in the gut microbiota of 10 IBRV-infected Angus calves (IBRV-positive group, P) compared with their 10 healthy counterparts (IBRV-negative group, N), as well as their correlations with MetaCyc metabolic pathways, were investigated using 16S rRNA sequencing. In comparison with N, both Simpson, Shannon and Pielou_e indices of alpha diversity were elevated in P, and the beta diversity showed a marked separation between N and P. The relative abundance of phylum Firmicutes_C was significantly increased, whereas that of phyla Bacteroidota, Cyanobacteria, and Firmicutes_D were reduced in P. The relative abundance of Genera Dialister and Klebsiella were enriched, while that of Lactobacillus and Blautia_A were depleted in P. Four distinct MetaCyc metabolic pathways were significantly altered, DENITRIFICATION-PWY, PWY-6906, and P101-PWY were significantly decreased in P, while PWY-7446 was significantly increased. Correlation analysis showed that in N, Faecalimonas was positively correlated with both P101-PWY and PWY-6906, and Limousia was positively correlated with P101-PWY. Faecalimonas was positively correlated with PWY-7446, and Klebsiella was positively correlated with DENITRIFICATION-PWY in P. Our results reveal that IBRV infection is associated with significant changes in the gut microbial community and its predicted metabolic functions, which may be linked to the host’s systemic response to the infection. This study provides preliminary data on the association between IBRV infection and gut microbiota profiles, laying a theoretical foundation for future investigations into IBRV pathogenesis and potential targeted prevention strategies.